"I choose fish": Understanding informal civil society in Vietnam through environmental grievances and actions. (June 2023) - Nguyen-Van-Quoc, Thai; Trell, Elen-Maarja
This paper focuses on informal civil society in an authoritarian context, particularly the unprecedented nation-wide protests and civic action in Vietnam, triggered by the industrial pollution and the resulting mass fish death on the central coast in 2016. We explore civil society actors' motivations and tactics to take action under political restrictions. Data was collected from semi-structured interviews with civil society actors. The findings illustrate how informal civil society in Vietnam is built on independent or partly NGO-affiliated individuals working together to promote non-violent change, although the process of doing so might involve challenging the government apparatus. The activists were motivated to take action by the dead fish' symbolism of endangered livelihood, environmental protection, and to demand transparency from the government. Critical factors further contributing to the mobilisation of citizens included the combination of food symbolism and anti-China nationalism, the tactical use of Facebook by urban activists, and religious leadership in the rural areas. The protests resulting from the coastal pollution can be seen as boundary-spanning events through which Vietnamese civil society actors 'invent' spaces of (political) participation amidst limited 'invited' space.